COMMUNICATIONS MANAGEMENT IN SCHOOL - TOTSEVA, Yanka (The Eurasia Proceedings of Educational and Social Sciences, 2015)
The report presents the results of multifactorial analysis of problems of communication management in school in the modern world and the role of the School principal as their manager. The paper brings out the specifics, events and trends and the analysis is done through the prism of school management and communication management. Some regulations are analyzed and techniques and tools to improve the quality of communication processes are proposed. In the XXI century we recognize the school: as a mediator between the individual and his/her own future (not as a special closed environment designed just for itself and only in the abstract future for something else); as a mediator in an attempt to reconcile the interests of its various users (children, parents, society) and to organize the dialogue between them; as an intermediary who tries to organize the transitions between school and non-school periods (family, school, profession) as organic moments of age and social maturation of the individual. School is an institution that has its historical and national circumstances, but now must be reformed very quickly in order to adapt to new realities and to meet the expectations of students and their parents. We considered various communication channels from the perspective of communication management and the influence of cultural factors on their effective use. Special emphasis is put on the use of new information and communication technologies and the opportunities they provide to enrich the communication. Finally we give recommendations for improving communications management in school, working definitions are given in an attempt to update the conceptual apparatus.